Climate change has already made the United States poorer - Derek Lemoine (Proceedings of the National Academy of Sciences, 2025)
The climate is already changing. The present study shows that these changes have already affected the U.S. economy. It develops a formal framework that accounts for how climate change has affected each county’s economy by altering current and past weather, both locally and elsewhere around the country. The results show that climate change is already reducing annual U.S. income by 0.32% [95% CI: −0.17 to 0.82%] by altering counties’ current, local temperatures, with losses concentrated in the Great Plains and Midwest. Accounting for effects on past temperatures and on temperatures in other counties increases income losses to 12% [2.0 to 22%] and makes them more widely distributed, with suggestive evidence that trade networks propagate effects around the United States. Central estimates can change with different indices of nonlocal weather or models of cross-county heterogeneity. Calculations like those developed here could be updated annually as a way of measuring and communicating the progress of climate change.